Effect of extrusion and turmeric addition on phenolic compounds and kafirin properties in tannin and tannin-free sorghum. (November 2021) - D'Almeida, Carolina Thomaz dos Santos; Mameri, Hamza; Menezes, Neuri dos Santos; de Carvalho, Carlos Wanderlei Piler; Queiroz, Valeria Aparecida Vieira; Cameron, L.C.; Morel, Marie-Hélène; Takeiti, Cristina Yoshie; Ferreira, Mariana Simões Larraz
Graphical abstract: Highlights: Phenolic profile and kafirin polymerization were investigated in sorghum extrudates. Metabolomics revealed distinguished phenolic profile in tannin-rich extrudates. Extrusion promoted the breakdown of bound phenolics and proanthocyanidin oligomeric. Extrusion improved kafirins solubility and can enhance their digestibility. Turmeric addition increased the phenolic content without impact on digestibility. Abstract: Sorghum is a potential substitute for corn/wheat in cereal-based extruded products. Despite agronomic advantages and its rich diversity of phenolic compounds, sorghum kafirins group together and form complex with tannins, leading to a low digestibility. Phenolic content/profile by UPLC-ESI-QTOF-MS E and kafirins polymerization by SE-HPLC were evaluated in wholemeal sorghum extrudates; tannin-rich (#SC319) and tannin-free (#BRS330) genotypes with/without turmeric powder. Total phenolic, proantocyanidin and flavonoid contents were strongly correlated with antioxidant capacity (r > 0.9, p < 0.05). Extrusion increased free (+60%) and decreased bound phenolics (−40%) in #SC319, but reduced both (−40%; −90%, respectively) in #BRS330, which presented lower abundance after extrusion. Turmeric addition did not significantly impact antioxidant activity, phenolic content and profile and kafirins profile. Tannins presence/absence impacted phenolic profiles and polymerization of kafirins which appears related to the thermoplastic process. The extrusion improved proteins solubility and can positively enhance their digestibility (phenolic compounds-proteins interactions), making more accessible to proteolysis in sorghum extrudates.